Young adult patients with squamous cell carcinoma of the tongue strongly express p16 without human papillomavirus infection. (2nd January 2019) - Tachibana, Tomoyasu; Orita, Yorihisa; Gion, Yuka; Miki, Kentaro; Ikegami, Kana; Marunaka, Hidenori; Makino, Takuma; Akagi, Yusuke; Akisada, Naoki; Tsumura, Munechika; Ito, Toshihiro; Yoshino, Tadashi; et al.
Abstract: Background: Long-term smoking and drinking are known to contribute to the onset of tongue cancer (TC). However, the increasing incidence of TC in younger adults has been suggested to be associated with other factors. Objectives: The present study investigated the relationship between TC and human papillomavirus (HPV) infection. Material and methods: Clinical records and surgically resected specimens from 86 patients (<40-years-old, n  = 12; ≥40-years-old, n  = 74) with TC were analyzed. Strong nuclear and cytoplasmic p16 staining was considered positive. HPV DNA (high-risk subtypes: 16, 18, 31, 33, 35, 52b, and 58; low-risk subtypes: 6 and 11) was detected using consensus primer-mediated polymerase chain reaction. Results: Strong p16 expression was observed in 10 (11.6%) patients. HPV DNA was detected in 9 (10.5%) patients (high-risk subtypes, n  = 2; low-risk subtypes, n  = 7). Strong p16 expression was observed more frequently among younger adults than among older adults (33.3% vs. 8.1%; p  = .045). p16 staining did not correlate with the detection of HPV DNA (correlation coefficient, 0.113; p  = .300). Conclusions and significance: In TC, p16 expression was not associated with HPV infection, suggesting that it may be caused by a different mechanism.